2019
DOI: 10.21597/jist.517739
|View full text |Cite
|
Sign up to set email alerts
|

Trace Element Analysis in Some Plants Species by Inductively Coupled Plasma Optical Emission Spectrometry (ICP-OES)

Abstract: In this study, the whole parts of eight edible and medicinal species (Alcea rosea, Carduus pycnocephalus subsp. albidus, Euphorbia gaillardotii, Euphorbia macroclada, Hypericum triquetrifolium, Kickxia lanigera, Malvella sherardiana and Mentha longifolia subsp. noeana were determined for their trace element (Al, As, B, Cd, Cr, Cu, Fe, Mn, Ni, Pb and Se) contents using ICP-OES. Before the whole plant parts were analyzed by ICP-OES, the porcelain crucibles were ashed and dissolved by adding concentrated nitric a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 22 publications
1
12
0
6
Order By: Relevance
“…24 The detected high concentrations of Fe and Zn in the samples of cultivated species of Mentha confirmed the results of previous published papers that the deficiency of Zn leads to a deficiency of Fe in plants. 24,25 Twelve elements (Na, K, Ca, Mg, Cr, Cu, Mn, Fe, Ni, Cd, Pb, and Zn) were compared in all Mentha samples by correlation analysis using Microsoft Excel. The element correlations (Pearson, r) in the studied wild and cultivated Mentha samples from various sampling sites are reported in Tables 3 and 4.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…24 The detected high concentrations of Fe and Zn in the samples of cultivated species of Mentha confirmed the results of previous published papers that the deficiency of Zn leads to a deficiency of Fe in plants. 24,25 Twelve elements (Na, K, Ca, Mg, Cr, Cu, Mn, Fe, Ni, Cd, Pb, and Zn) were compared in all Mentha samples by correlation analysis using Microsoft Excel. The element correlations (Pearson, r) in the studied wild and cultivated Mentha samples from various sampling sites are reported in Tables 3 and 4.…”
Section: Resultssupporting
confidence: 90%
“…Relatively low content of Cu in wild samples compared to the content of Zn is due to the fact that higher Cu concentrations mean lower Zn content, because higher concentrations of Cu in the soil relative to Zn can reduce the availability of Zn to a plant, due to competition for the same sites for absorption into the plant root. [23][24][25] In cultivated herb samples (Table 2), no Cd was detected in all three samples, while the highest concentration was detected for Fe and the lowest concentrations for Pb. 24 The detected high concentrations of Fe and Zn in the samples of cultivated species of Mentha confirmed the results of previous published papers that the deficiency of Zn leads to a deficiency of Fe in plants.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Aluminium and chromium contents were detected in the range of 190.16-638.40 ng/mg and 0.91-2.71 ng/mg, respectively. In Yener's study, the Al and Cr contents were found 1424 and 4.8 mg/kg in Malvella sherardiana (20). In another study, heavy metal analysis of 20 medicinal plants was performed, and the highest chromium value was found to be 33.75 µg/g (21).…”
Section: Concentrations Of Trace Elements In Achillea Speciesmentioning
confidence: 94%